PENGARUH LINGKUNGAN KERJA, STRES KERJA, PENDIDIKAN DAN PELATIHAN TERHADAP KINERJA ASN PADA DINAS KOPERASI DAN USAHA MIKRO KABUPATEN SITUBONDO - Nurul Fajrin Imaningrum; Edy Kusnadi Hamdun; Siti Soeliha (Jurnal Mahasiswa Entrepreneurship (JME), 2026)
This study aims (1) to determine the partial effect of work environment, work stress, education and training on the performance of state civil servants (ASN) (2) to determine the simultaneous effect of work environment, work stress, education and training on the performance of state civil servants (ASN) (3) to determine the work environment, work stress, education and training which have a dominant influence on the performance of the State Civil Apparatus (ASN). The method used is multiple linear regression analysis, t test, f test, dominant test and the coefficient of determination. The result of this research is multiple linear regression equation Y = 4.164E-17 + 0.378 X1 - 0.374 X2 + 0.348 X3 + e. T-test for the work environment variable (X1) tcount 2.803 > ttable 2.030, work stress variable (X2) tcount -2,973 < ttable -2,030 and education and training variables (X3) tcount 2,547 > ttable 2,030. Then these variables have a partial influence with a positive significant level on the variable Performance of the State Civil Apparatus (ASN) (Y). Simultaneous statistical test or F test shows Fcount > Ftable, 10,842 > 2,87 so it can be concluded that the work environment, work stress, education and training have a simultaneous effect on the performance of the State Civil Apparatus (ASN). Based on the dominant test, the value of the work stress variable (X2) is -2,973, which is greater than the work environment (X1) and education and training (X3) variables.